MEMBANGUN KEBIJAKAN PUBLIK UNGGUL DI ERA DEMOKRASI - Riant Nugroho (Jurnal Academia Praja, 2018)
The superiority of a nation is increasingly determined by the Government's ability of the nation to produce superior policies. The era of Indonesian democracy since the 1998 Reformation has not yet promised a public policy blow. The question is how to build capacity to build superior public policy. The answer is offered in the form of Ten Principles (also called "Laws") of Public Policy. They are ―Public‖, ― A Point of No Return‖, ―Great, not Good‖, ―Management, not politics‖, ―Moral, not technical‖, ― A system, not units‖, ―A Gift‖, ―Honor‖, ―Glorify’, and ―Learning‖. The performing policy in various places, at various times, in various governments were cored on the principles, and it will be in the next future.